Pemberdayaan Kelompok Usaha Wanita Tani Mekar Melalui Implementasi Teknologi Tepat Guna Untuk Peningkatan Produktivitas dan Kualitas Kopi Lokal Sinjai Borong - Mado, Irwan; Nur Abdi, Muhammad; Nanda, Sahabuddin; Muhsin, Muh Arief (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
The MEKAR Women Farmers' Group (KWT) is a group of women farmers engaged in coffee processing in Pasir Putih Urban Village, Sinjai Borong District, Sinjai Regency. Despite the significant potential for coffee production, economic value-added remains limited because post-harvest processes specifically dry hulling and drying are still conducted using traditional methods that rely heavily on weather conditions. This community service program aims to enhance KWT MEKAR’s production capacity and coffee quality through the application of appropriate technology and human resource capacity building. Implementation utilized a participatory approach comprising program outreach, training on huller machine operation, operational guidance for the technology, the construction of a practical coffee drying unit, and training on coffee management and quality improvement. The results demonstrate improved member proficiency in operating coffee processing technology, a better understanding of post-harvest quality control, and the availability of production technology that enhances processing efficiency. This program contributes to the economic strengthening of women farmers and increases the value-added of local commodities, while also supporting the achievement of the Sustainable Development Goals (SDGs) through women's empowerment and sustainable economic development.